Experimenting with the Art of Observation. (3rd April 2022) - Parker, Heather; Brown, Shannon; Morehead, Allison; Dempster, Madeleine; Wagner, Natalie; Curtis, Rachel; Law, Christine
ABSTRACT: This case study of an art education program for medical students examines the efficacy of different types of content and modes of delivery. Through the delivery of art analysis, art history, sculpting, and life drawing seminars, art educators were able to teach empathy, observation, and flexible thinking to first-year medical students. This interdisciplinary approach to museum education can be used across many contexts to complement existing curricula.